Expressions of Americanism in “The thin red line” (1998) = Biểu hiện của chủ nghĩa Mỹ trong bộ phim “The thin red line” (1998) - Nguyễn, Diệu Hồng (2021)
Since its founding, the United States has become arguably the most dominant country in the world, influencing the global culture through economy, politics, and most interestingly, media. Since its invention in the late 1800s, movies have remained one of the most prominent media. This paper takes the features of Americanism to task and investigates its representations in the movie The Thin Red Line, which is cited as one of the best war movies in Hollywood cinema history. This paper first investigates how the features of Americanism are expressed in the movies; second, it analyzes the socio-cultural and creative factors that came to influence the movie. By using visual analysis to investigate the meanings of the images presented in the movie, and analyzing characters, the author seeks patterns that allow the themes of self-government, unity and sacrifice to emerge and analyze their representations. This paper lists some of the most influential time periods in American history and their effects on shaping the definitions of Americanism which are used in this paper, and investigates their political and social landscapes to further understand its consequences and effects on the portrayals of Americanism in the movie.